PENERAPAN EKSTRAKURIKULER TARI DALAM MENGEMBANGKAN KETERAMPILAN WIRAGA, WIRAMA, DAN WIRASA SISWA SDN 2 PLAWANGAN - Widyawati; Fera Dwidarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education in primary schools aims not only to develop students' academic abilities, but also to shape their character and skills. One way to shape character is through extracurricular dance activities. The purpose of this study is to describe the implementation of extracurricular dance activities in developing students' skills in wiraga (movement), wirama (rhythm), and wirasa (expression) at SDN 2 Plawangan. This study employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The subjects of this study include the teacher-mentor as the coach and the students participating in the activity. The study indicates that through this extracurricular activity, positive contributions can be made to the development of the three aspects of dance skills.